PREDICTION OF MEDICAL HAZARDOUS WASTE GENERATION FROM COVID-19 PATIENT HANDLING HOSPITALS - Mr Prihartanto (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
The Covid-19 pandemic disaster has resulted in thousands peoples died and hospitalized. Handling of Covid-19 patients requires more medical equipment than normal condition, such as masks, goggles, protective clothing and so on which will increase the rate of generation of medical waste. Prediction of the total medical hazardous waste generation in Indonesia can be calculated using the prediction model of the total number of Covid-19 cases and the average generation of medical waste for each one patient. In this study, the capacity of a hazardous waste incinerator in Indonesia is also calculated to determine the time needed for waste processing. Besides, standar procedures for handling medicalÂ  hazardous waste from source to final disposal site are also needed.